(untitled) (Revista Linhas, 2007)
O artigo trata de resultados de pesquisa de mestrado em Educação e Cultura da UDESC que tem por objeto a representação da mulher na Música Popular Brasileira (MPB) na década de setenta do século XX. Pretende demonstrar as etapas desse estudo que possibilitaram identificar as diversas representações de mulheres encontradas na MPB na década acima referida. As representações foram encontradas a partir do procedimento da análise de discurso das letras de músicas dos três primeiros discos long playing[1] colocados em dois grandes centros urbanos, Rio de Janeiro e São Paulo. Os dados foram extraídos das pesquisas do IBOPE (Instituto Brasileiro de Pesquisa e Opinião Pública) mantidas pelo AEL (Arquivo Edgard Leuenroth) da UNICAMP. PALAVRAS-CHAVES: Representação Social. Estudos da Mulher. Música Popular Brasileira. The article, that has as object the woman’s representation in the Brazilian Popular Music (MPB) in the seventies, is the result of my Master Degree research in Education and Culture of UDESC. It intents to demonstrate the stages of this study that allowed to identify the several representations of women found in the MPB during the decade mentioned above. The representations were found through the discourse analysis proceeding of the lyrics in the three first long playing records divided into two big urban justifys, Rio de Janeiro and São Paulo. The data were extracted from the researches of IBOPE (Brazilian Institute of Research and Public Opinion) supported by AEL (Edgard Leuenroth Archive) of the UNICAMP. KEY-WORDS: Social Representation. Woman’s Studies. Brazilian Popular Music